Xúc tác trên cơ sở kim loại trong phản ứng epoxy hoá dầu đậu nành - Thủy, Nguyễn Thị; Đức, Vũ Minh; Quý, Phan Ngọc; Liêm, Nguyễn Thanh (Vietnam Journal of Chemistry, 2015)
An epoxidation of vegetable oil is an oxidation reaction of double bond in the presence of catalysts, wherein hydrogen peroxide is commonly used as the oxidant. Depending on catalyst, the reaction is carried out via different methods. The conventional epoxidation of vegetable oils catalyzed by liquid inorganic acids have several drawbacks, including: the reaction time is long; it is very difficult to control side reactions; the yield of reaction is relatively low. On the contrary, the reaction using metal-based catalysts can overcome such disadvantages. Those catalysts which based on various metals such as Mo, Ti, Co, Ni, Pt, Fe, and W... are used for the epoxidation of alkenes and fatty esters by many scientists in the world. Some preliminary results on the epoxidation of soybean oil over tungsten-based catalyst have been reported in this paper. The successful epoxidation of the soybean oil was confirmed by the FTIR analysis. The effects of the H2O2 oxidant as well as tungstate concentration on the epoxidation process were investigated by determining the epoxy content of the obtained products. The yield and double bond conversion of the reaction are also studied in order to evaluate the efficiency of the catalyst. After 1 hour of reaction, 90.31÷90.39 % of double bonds was disappeared, 91.14÷91.56 % of which were converted to epoxy groups, therefore the yield of the reaction was between 82.31÷82.76 %. Those results indicated that using the metal-based catalyst was considerably minimized side reactions.